Kinerja dan Kendala Manajemen Logistik Tim Reaksi Cepat (TRC) di BPBD Kabupaten Gunung Kidul - Dedi Prayitno; Furoida Alfi Fairus (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
Natural disasters are conditions that cannot be predicted with certainty. Everyone hopes to avoid any disaster. Without exception, either natural disasters or other disasters that can make people suffer both physically and psychologically. Humans can prepare to be able to anticipate various events that will occur at any time. Anticipation can be done on a small scale/family or mass/regional scale, starting from the preparation of infrastructure, preparing an emergency system, what to do in the event of a disaster and so on. Operations of facilities and infrastructure, human resources and systems for anticipating / dealing with natural disasters are carried out by local and central governments in this case BPBDs such as the Rapid Response Team in Gunung Kidul must be in sync and optimally. The Rapid Response Team (TRC) has a large role in disaster management activities. The Rapid Response Team (TRC) carries out various activities, one of which is disaster mitigation. Disaster mitigation is carried out with the aim of minimizing the risk of a disaster occurring. In addition to disaster mitigation, the Rapid Response Team (TRC) conducts a rapid study of the ongoing disaster so that further action can be taken to overcome the disaster. To improve the performance of the Rapid Reaction Team (TRC), several efforts were made in accordance with the explanation given by the resource coordinator for the Rapid Reaction Team (TRC). The existence of disaster management equipment is able to assist the Rapid Response Team (TRC) in carrying out their duties to be more optimal, effective, and efficient. Keywords: Logistics management, disaster, performance, management